Challenges in the regularization of informal settlements in Epworth: a case of Epworth local board - Moyo, Marx Konias (Midlands State University, 2017)
Local authorities in Zimbabwe have been facing a plethora of challenges due to the mushrooming of informal settlements. About 90% and above of the Zimbabwean population is moving to towns posing a bigger challenge to the management of towns and cities. The 2005 operation Murambatsvina cleaned all the illegal activities and people residing near Harare found solace and cheap shelter in Epworth. The Operation Garikai which superseded Murambatsvina failed to deliver as it was promised hence it became a failure. The population in Epworth grew at a faster rate after 2005 due to the operation Murambatsvina. Urban councils are not silent about all this. Councils are partaking in legal stand allocations to ease the situation. There has been regularisation process by the Council of Epworth to provide formal stands and deal with the land barons once and for all. People who had got stands illegally think they should be given their bigger stands despite regularisation. There are crooks who still believe they can benefit by creating chaos. The research therefore seeks to achieve the following objectives which are to determine causes of citizen resistance, to find out the importance of development in modern day governance, to come up with better remedy to resistance and determine the total populace that is supporting council programs and those that are against it and lastly to identify causes of the sprawling urban informal settlements in Epworth and to come up with the conclusion and recommendations on how to counter resistance. Ways of countering citizen resistance in this research include engagement and involvement, use of legislation and use of awareness campaigns. Both qualitative and quantitative research design to the targeted individuals who included council officials, residents and civil societies. The research used purposive and systematic sampling. The researcher administered questionnaires to the council and residents. Observation and interviews were also conducted. To deal with land barons once and for all, to rid of all political party leadership that pounce on unsuspecting and vulnerable home seekers, the game of voting extended to squatters create problems for local authority as politics tends to be dirty when the law is applied impartially. E.L.B has to be efficient and effective in the discharge of its duties so as to minimise resistance.